Interfacility transfer communication of multidrug-resistant organism colonization or infection status: Practices and barriers in the acute-care setting. (16th April 2022) - Ellingson, Katherine D.; Noble, Brie N.; Buser, Genevieve L.; Snyder, Graham M.; McGregor, Jessina C.; Rock, Clare; Chopra, Teena; Mody, Lona; Furuno, Jon P.
Abstract: Objective: To describe interfacility transfer communication (IFTC) methods for notification of multidrug-resistant organism (MDRO) status in a diverse sample of acute-care hospitals. Design: Cross-sectional survey. Participants: Hospitals within the Society for Healthcare Epidemiology of America (SHEA) Research Network (SRN). Methods: SRN members completed an electronic survey on protocols and methods for IFTC. We assessed differences in IFTC frequency, barriers, and perceived benefit by presence of an IFTC protocol. Results: Among 136 hospital representatives who were sent the survey, 54 (40%) responded, of whom 72% reported having an IFTC protocol in place. The presence of a protocol did not differ significantly by hospital size, academic affiliation, or international status. Of those with IFTC protocols, 44% reported consistent notification of MDRO status (>75% of the time) to receiving facilities, as opposed to 13% from those with no IFTC protocol ( P = .04). Respondents from hospitals with IFTC protocols reported significantly fewer barriers to communication compared to those without (2.8 vs 4.3; P = .03). Overall, however, most respondents (56%) reported a lack of standardization in communication. Presence of an IFTC protocol did not affect whether respondents perceived IFTC protocols as having a significant impact on infection prevention or antimicrobial stewardship. Conclusions: Most respondents reported having an IFTC protocol, which was associated with reduced communication barriers at transfer. Standardization of protocols and clarity about expectations for sending and receipt of information related to MDRO status may facilitate IFTC and promote appropriate and timely infection prevention practices.